Administrative-legal regulation of causes and conditions determining corruption in social sphere - A. V. Polukarov (Russian Journal of Economics and Law)
Objective: to show the capabilities of administrative-legal regulation for combating the causes and conditions determining corrupt behavior in the social sphere.Methods: dialectic approach to cognition of social phenomena, enabling to analyze them in historical development and functioning in the context of the totality of objective and subjective factors that determined the choice of the following research methods: analysis, synthesis, comparison, systematic, formal-legal, comparative-legal methods.Results: the reasons and conditions determining the corruption in the social sphere were disclosed; this leads to the conclusion that corruption counteraction should be based on: 1) recognition of the social sphere as the key object of protection against corruption; 2) elaboration of special administrative-legal means of corruption counteraction in the social sphere. It is necessary to take into account the features of social relations in such sectors as education, healthcare, culture, physical culture and sports, etc. A number of foreign countries took the path of developing legislation on corruption counteraction taking into account the specifics of various social sphere segments functioning. This experience is quite interesting from the viewpoint of developing means of combating the causes and conditions that determine corruption in the social sphere. A number of the Russian Federation subjects also elaborate regional programs of combating corruption in education, healthcare, and culture. In our opinion, this experience should be transferred to the federal level of legal regulation. This will help to create a full-fledged system of corruption counteraction in the social sphere, taking into account different levels of its functioning. Scientific novelty: for the first time in administrative-legal science, the “law of torts aspect of corruption in the social sphere” issue is considered; the work reveals the causes and conditions that determine corruption in the social sphere, and gives their classification according to certain criteria. Basing on the study, the proposals are formulated, aimed at improving implementation of administrative and legal measures influencing the causes and conditions that determine corruption in the social sphere. Practical significance: the proposed legal and administrative means enable to form the administrative-legal regime aimed at minimizing the causes and conditions that determine corruption in the social sphere.